Penile urethral resection and anastomosis augmentation with regional tissue tension relieving technique: A cadaveric mechanical study and clinical outcome in two dogs. Issue 4 (24th March 2021) - Bertran, Judith; Ham, Kathleen M.; Gibson, Jordan F.; Litsky, Alan; Kieves, Nina R.
Abstract: Objective: To describe penile urethral augmentation anastomosis (PURAA) for resection anastomosis (RA) of the canine penile urethra by using autogenous tissue in two dogs and to determine the mechanical properties of the augmentation technique in cadaveric specimens. Study design: Cadaveric study and two case reports. Animals: Sixteen canine cadavers and two dogs with urethral obstruction. Methods: The lower urogenital system was harvested from cadavers and randomized into two groups: simple (S) and augmented (AUG) RA of the urethra. Tensile strength and peak load were compared between the two groups. Two dogs were treated with PURAA for urethral obstruction secondary to juxtaurethral neoplasms. Results: Minimal tensile strength (MITS) and maximal tensile strength (MATS) were greater in the AUG group (MITS, 54.36 ± 24.0 N; MATS, 75.37 ± 34.79 N) compared with the S group (MITS, 11.78 ± 4.93 N, P = .0014; MATS, 13.74 ± 3.89 N, P = .0015). Both dogs recovered without complications. Histopathological examinations were consistent with a lipomatous mass in both cases. Both dogs had good medium‐to‐long‐term outcomes. Conclusion: The augmentation technique improved the tensile properties of penile RA in normal cadavers and was associated with successful outcomes in two dogs. Clinical significance: Penile urethral augmentation anastomosis may help prevent stricture or leakage secondary to tension at the surgical site after penile urethral RA.